Penghasilan pasu organik penghalau-serangga terbiodegradasi (Development of organic insect-repellent biodegradable pot) / Nur Atirah Hasmi …[et al.] - Hasmi, Nur Atirah; Azman, Siti Sarah; Musa, Nadia Nisha; Wan Anuar, Wan Nurul Hidayah; Rodzali, Nur Nadirah (Universiti Teknologi MARA, 2020)
The potential of natural organic compounds as a repellent in biodegradable organic pot is budding into one of the new agriculture innovation. The use of recyclable materials in the production of the pot can reduce the excessive waste disposal problem and thus prevent pollution problems. The objectives are to recycle old newspapers into biodegradable pot for seedling of plants and to repel plant insect pests using organic compounds (Pandanus sp., Petroselinum crispum and Alium sativum). The production of the biodegradable pot incorporates the use of waste materials such as old newspapers and coconut husk together with natural organic materials such as tapioca flour, Pandanus amaryllifolius (pandan leaf), Petroselinum crispum (parsley) and Alium sativum (garlic). This product is distinguishable among others as it is environmental-friendly since the pot can naturally break over time (biodegradable). The aroma from the Pandanus amaryllifolius, Petroselinum crispum and Alium sativum can repel flying and crawling insect that may attack the crops. The organic insect-repellent biodegradable pot has a potential in replacing plastic polybags since the crops planted in the pot can be directly replanted in the soil without the need of disposing the pot. Root is allowed to grow through the pot where later on, it will be degraded. Apart from that, this pot has high commercial values since it is easy to be handled, low in production cost, eco-friendly where only recyclable and natural organic materials were used, and the most crucial point is it can act as an insect repellent.